Intraoperative Steroid Use and Outcomes Following the Norwood Procedure: An Analysis of the Pediatric Heart Network's Public Database. Issue 1 (January 2016) - Elhoff, Justin J.; Chowdhury, Shahryar M.; Zyblewski, Sinai C.; Atz, Andrew M.; Bradley, Scott M.; Graham, Eric M.
Abstract : Objective: Data supporting the use of perioperative steroids during cardiac surgery are conflicting, and most pediatric studies have been limited by small sample sizes and/or diverse cardiac diagnoses. The objective of this study was to determine if intraoperative steroid administration improved outcomes following the Norwood procedure. Design: A retrospective analysis was performed on the 549 neonates who underwent a Norwood procedure in the publicly available datasets from the Pediatric Heart Network's Single Ventricle Reconstruction trial. Groups were compared to determine if outcomes differed between intraoperative steroid recipients ( n = 498, 91%) and nonrecipients ( n = 51, 9%). Setting: Fifteen North American centers. Subjects: Infants enrolled in the Single Ventricle Reconstruction trial. Interventions: None. Measurements and Main Results: Baseline characteristics and intraoperative variables were similar between groups with the exception of a shorter duration of cross clamp and cardiopulmonary bypass time in the group that received steroids. Subjects who did not receive intraoperative steroids had improved hospital survival (94% vs 83%, p = 0.03) but longer ICU stays (16 d; interquartile range, 12–33 vs 14 d; interquartile range, 9–28; p = 0.04) and hospital stays (29 d; interquartile range, 21–50 vs 23 d; interquartile range, 15–40; p = 0.01) than steroid recipients. In multivariate analysis, lengths of stay associations were no longer significant, but hospital survival trended toward favoring the nonsteroid group with an odds ratio of 3.52 (95% CI, 0.98–12.64; p = 0.054). Conclusions: In the large multicentered Single Ventricle Reconstruction trial, there was widespread use of intraoperative steroids. Intraoperative steroid administration was not associated with an improvement in outcomes and may be associated with a reduction in hospital survival in neonates undergoing the Norwood procedure. This study highlights the need for a randomized control trial. Abstract : Supplemental Digital Content is available in the text.